Research on Two-way Promotion Mechanism of Digital RMB and Digital Economy - Lyu, Wenbo; Lei, Zhehao (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
The two-way promotion mechanism between digital RMB and the digital economy is a research topic of great concern in the field of fintech. From the perspective of promoting the development of the digital economy, the promotion and application of digital RMB can promote the intelligentization, convenience and security of payment methods, and provide a more efficient and convenient way for data circulation. This convenience will help expand the e-commerce market scale and activate consumer demand, and at the same time provide new ideas and support for the transformation and upgrading of traditional industries. Secondly, the digital economy also plays a key role in digital currency innovation. Due to the large volume and fast speed of the digital economy, an instant and low-cost payment system is needed. By analyzing the mutual influence of digital RMB on the development of the digital economy and digital economy on digital currency innovation, this paper uses empirical analysis and intuitive data to reveal the inseparable connection and interaction between the two, aiming to explain the relationship between digital RMB and digital economy that is mutually complementary, symbiotic and prosperous. Through an in-depth discussion of the technical, policy and market factors covered by the close relationship between the two, it provides a theoretical basis for building a more healthy, stable and dynamic modern financial ecosystem.